Kinerja usahatani dan pemasaran terong ungu di Kabupaten Kupang, Nusa Tenggara Timur - Diah Aprilia Bau Bani; Doppy Roy Nendissa; I Wayan Nampa (Journal of Agricultural Socio-Economics (JASE), 2020)
Purple eggplant is becoming a popular plant cultivated, especially by small farmers in Kupang, East Nusa Tenggara (NTT). The purpose of this study was to measure the farm performance and marketing of purple eggplant. The research method used a survey method, using 46 sample farmers obtained by simple random sampling—the standard of eggplant cultivation measures farming performance. Business feasibility uses R/C ratio and marketing performance using Margin and Farmer Share (FS) and the marketing function. The results showed that the farming performance, as seen from the cultivation of purple eggplant, showed that every cultivation activity carried out by the farmer had almost fulfilled the ideal growth requirements according to the farmer's expectations with a production yield of 7.476 ton / 0.3ha. The income of purple eggplant farming is Rp. 3,033,840/the land area/planting season once. Purple eggplant farming is feasible, indicated by R/C> 1—marketing of purple eggplant through 4 marketing channels. The marketing system for eggplant is quite good, as indicated by the FS of 41.66%. Not many marketing functions are carried out at each stage so that not much-added value is generated. It is necessary to improve the purple eggplant cultivation system and increase the marketing function to increase the added value of purple eggplant.